2009
DOI: 10.2967/jnumed.108.056556
|View full text |Cite
|
Sign up to set email alerts
|

PET-Based Biodistribution and Radiation Dosimetry of Epidermal Growth Factor Receptor–Selective Tracer 11C-PD153035 in Humans

Abstract: The present study estimated the biodistribution and radiationabsorbed dose of epidermal growth factor receptor (EGFR) radioligand 11 C-PD153035 in whole-body PET examinations of healthy volunteers. Methods: Two-dimensional whole-body PET was performed on 9 subjects after injection of 11 C-PD153035 at 329.3 6 77.8 MBq (mean 6 SD). A total of 12 frames were acquired for approximately 90 min in 7 segments of the body. Regions of interest were drawn on PET images of source organs. Residence time was calculated as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 22 publications
1
47
0
Order By: Relevance
“…Tracer metabolism was not considered in those studies, and our results indicated that radiometabolites in tissue might make it difficult to detect blocking effects. The biodistribution and excretion of [ 11 C]PD153035 observed in the present study were similar to those reported for humans (12). These data suggest that metabolic and excretory behaviors are similar and, therefore, that our findings may have good translational potential.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Tracer metabolism was not considered in those studies, and our results indicated that radiometabolites in tissue might make it difficult to detect blocking effects. The biodistribution and excretion of [ 11 C]PD153035 observed in the present study were similar to those reported for humans (12). These data suggest that metabolic and excretory behaviors are similar and, therefore, that our findings may have good translational potential.…”
Section: Discussionsupporting
confidence: 78%
“…Promising in vivo results were observed in rodents (9)(10)(11). The tracer, labeled at position 6, was evaluated for radiation dosimetry (12) and for imaging of non-small cell lung cancer in humans; the uptake of radioactivity was positively correlated with an increased effectiveness of EGFR-directed therapy (13). However, our previous in vitro study indicated that the radiotracer was rapidly metabolized by both rat and human liver microsomes (14).…”
mentioning
confidence: 98%
“…In the domain of reversible anilinoquinazoline chemical moieties, many drugs and their derivatives such as PD 153035, gefitinib, erlotinib, ZD 6474, and ML01 were labeled with diverse radionuclides such as 11 C, 123 I, 125 I, 18 F (17,18,20-22), and the radiometal 99m Tc using 2 different chelators (23). Among all these labeled reversible inhibitors, 11 C-PD153035 was the only one whose biodistribution and dosimetry were recently evaluated in healthy volunteers (22) and indicated a favorable radiation dose profile. These reversible compounds were labeled either at the functional group at the 6-or 7-position of the quinazoline ring or at the anilino moiety (Fig.…”
Section: Approaches For Imaging Egfr In Cancermentioning
confidence: 99%
“…We previously demonstrated preclinically that 11 C-PD153035 tumor uptake correlates with EGFR expression (10) and characterized its biodistribution in healthy human volunteers as well as demonstrated tumor uptake in patients with NSCLC (11). Therefore, 11 C-PD153035 PET/CT has the potential to serve as an imaging biomarker for predicting which patients will benefit most from EGFR-TKI treatment.…”
mentioning
confidence: 99%